Rumen-protected methionine supplementation improves lactation performance and alleviates inflammation during a subclinical mastitis challenge in lactating dairy cows - A. Paz; T.C. Michelotti; M. Suazo; J. Bonilla; M. Bulnes; A. Minuti; D. Luchini; E. Trevisi; A.F. Lima; J. Halfen; M. Rovai; J.S. Osorio (Journal of Dairy Science)
ABSTRACT: This study aimed to evaluate the effects of rumen-protected Met on lactation performance, inflammation, and immune response, and liver glutathione of lactating dairy cows during a subclinical mastitis challenge (SMC). Thirty-two Holstein cows (145 ± 51 DIM) were enrolled in a randomized complete block design. At −21 d relative to the SMC, cows were assigned to dietary treatments, and data were collected before and during the SMC. Cows were blocked according to parity, DIM, and milk yield and received a basal diet (17.4% CP; Lys 7.01% MP and Met 2.14% MP) plus 100 g/d of ground corn (CON; n = 16) or a basal diet plus 100 g/d of ground corn and rumen-protected Met (SM, Smartamine M at 0.09% of dietary DM; n = 16), fed as a top-dress. At 0 d, the mammary gland's rear right quarter was infused with 100,000 cfu of Streptococcus uberis (O140J). Milk yield was recorded twice daily from 0 until 3 d relative to SMC. Milk samples were collected during each milking from 0 to 3 d relative to SMC, blood samples were collected at 0, 6, 12, 24, 48, and 72 h relative to SMC. The mTOR pathway activation was assessed in immune cells in blood and milk samples by measuring quantity and phosphorylation status of mTOR-related proteins, including AKT, S6RP, and 4EBP1. For the ratio of phosphorylated to total AKT, S6RP, and 4EBP1, blood samples were collected at 0, 12, and 24 h, and milk samples at 24 h relative to SMC. Liver biopsies were performed at −10 d and 24 h relative to SMC for measurement of glutathione. Linear mixed models with repeated measures were used to analyze the results. There was a trend for greater milk yield per milking (+ 0.8 kg) and per day (+1.7 kg) after SMC in SM cows compared with CON. The DMI was not affected by dietary treatments. Reactive oxygen metabolites were lower in SM cows than in CON. Milk somatic cell linear score was not affected by dietary treatments, and a score >4 at 24 h confirmed subclinical mastitis. The SM cows had greater milk fat percentage at 24 and 36 h post SMC, resulting in overall greater milk fat. Milk protein tended to be greater in SM cows than in CON. We observed greater liver glutathione in SM cows than in CON. Among inflammation biomarkers, ceruloplasmin was lower for SM cows compared with CON. In milk, greater phosphorylated (p) AKT:AKT and pS6RP:S6RP ratios were observed in immune cell populations from SM cows compared with CON. Blood neutrophils had a greater p4EBP1:4EBP1 ratio in SM cows compared with CON. Overall, our results show that Met supplementation during an SMC positively affected milk performance, lowered the risk of oxidative stress, and attenuated inflammation partially by increasing liver glutathione and immune cells' protein synthesis via mTOR signaling.